Twenty Years of the EU‐Turkey Customs Union: A Synthetic Control Method Analysis*. (20th October 2016) - Aytuğ, Hüseyin; Kütük, Merve Mavuş; Oduncu, Arif; Togan, Sübidey
Abstract: The paper studying the 1995 EU–Turkey Customs Union (CU) delivers a quantitative assessment of trade and GDP per capita effects of the CU on the Turkish economy. Our Synthetic Control Method based analysis reveals, contrary to the results of most studies in the literature, that the CU's effects have been substantial by any standards. In particular, the paper shows that in the absence of the EU–Turkey CU, Turkish exports to the EU and GDP per capita would have been 38 per cent and 13 per cent less, respectively.